2010
DOI: 10.1021/jf9039827
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies on Chemical and Textural Modifications in Gelatin Films by Reaction with Glyoxal and Glycolaldehyde

Abstract: The present study investigated chemically modified gelatin biopolymer films. Gelatin solutions were treated with glyoxal and glycolaldehyde, respectively, at concentrations ranging from 0.25 to 7.5 wt % based on gelatin. From these solutions, films were produced under defined conditions and characterized with different chemical and physical methods. N(epsilon)-carboxymethyllysine (CML), glyoxal-derived lysine dimer (GOLD), and 5-(2-imino-5-oxo-1-imidazolidinyl)norvaline (imidazolinone) were analyzed as chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…Another widely used dialdehyde is glyoxal. Similar results introduced by crosslinking with glyoxal were observed, such as a significant increase in strength and modulus of compression‐molded wheat gluten protein–based polymers at a relative humidity of 50%, an increase in water‐resistance properties and stiffness but a decrease in elongation of the wet‐cast gelatin biopolymer films, a decrease in the diameter of the electro‐spun zein fibers, and enhancement of the mechanical properties …”
Section: Crosslinkingsupporting
confidence: 75%
See 1 more Smart Citation
“…Another widely used dialdehyde is glyoxal. Similar results introduced by crosslinking with glyoxal were observed, such as a significant increase in strength and modulus of compression‐molded wheat gluten protein–based polymers at a relative humidity of 50%, an increase in water‐resistance properties and stiffness but a decrease in elongation of the wet‐cast gelatin biopolymer films, a decrease in the diameter of the electro‐spun zein fibers, and enhancement of the mechanical properties …”
Section: Crosslinkingsupporting
confidence: 75%
“…For example, Spanneberg et al . reported that the mechanisms of protein modification by glyoxal and glycolaldehyde were different . Arginine was the major target to be modified by glyoxal, while glycolaldehyde reacted almost exclusively with lysine and other amino groups.…”
Section: Crosslinkingmentioning
confidence: 99%
“…Approximately 90% of the lysine modifications could not be accounted for. In addition, these authors showed that lysine was preferentially modified by GA as there was much less loss of arginine residues [31]. In our study, we did not analyze arginine because bLG contains only three arginine residues per molecule, whereas there are 16 lysine residues.…”
Section: Discussionmentioning
confidence: 86%
“…We did not analyze for other modifications as our analytical method is restricted to the detection and quantification of these modified amino acids [28]. Spanneberg et al [31] recently described the glycation of gelatin by GA. Similar to our findings, these authors detected only minor amounts of CML but no glyoxal-derived lysine dimer or imidazolinone.…”
Section: Discussionmentioning
confidence: 99%
“…Glycolaldehyde was first identified as a fermentation inhibitor in our previous study (Jayakody et al 2011). Glycolaldehyde is formed by a retro-aldol condensation from sugars such as hexoses and pentoses during the treatment of cellulose and hemicellulose with hotcompressed water (Sasaki et al 2002;Kabyemela et al 1998;Sakaki et al 1996;Richards 1987). The toxicity of glycolaldehyde has been considered to be caused by its molecular feature of α-hydroxyaldehyde, which forms a Schiff base with the amino bases of proteins and is followed by an Amadori rearrangement, conversion to aldoamine, regeneration of a carbonyl base, and cross-linking of proteins (Acharya and Manning 1983) or formation of carboxymethyllysine and related advanced glycation end-products (Spanneberg et al 2010;Takeuchi et al 2000;Glomb and Monnier 1995). However, the mechanism of its toxicity, its detoxification mechanism, and its metabolic fate in a reductive environment have remained largely unknown.…”
Section: Introductionmentioning
confidence: 99%